Aggression in Pornography Myths and Realities - Seida, Kimberly (2020)
Aggression in Pornography focusses on the issue of violence in mainstream pornography and examines what we know, what we think we know, and what are some surprising research findings and insights about the place of violence within pornography today. The authors first review the modern pornography industry, theoretical claims about pornography as violence, and the ways in which aggression has been defined and measured in previous research. Next, they review the findings of empirical research on violent content in pornographic materials and the potential effects of such content on audiences. The main part of the book relies on systematically collected empirical data, as the authors analyze the content of hundreds of pornographic videos as well as more than a hundred interviews with men and women who regularly watch pornography. These analyses provide surprising insights regarding the prevalence of and trends in violent content within mainstream pornography, the popularity of violent and non-violent content among viewers, and variations in aggression by race and sexual orientation. As such, Aggression in Pornography will be of interest to students and researchers in sociology, gender and sexuality studies, and media and film studies, as well as to wider audiences who are interested in today's pornography industry and to policymakers looking to devise empirically driven policies regarding this industry and its potential effects.